2022
DOI: 10.1021/acs.jpcc.1c07549
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Amino-thiolysis Cyclization of Graphene Oxide Modified with Sulfur Dioxide: XPS and Solid-State NMR Studies

Abstract: Graphite microparticles were oxidized to graphene oxide (MPGO) by Hummers' method followed by thermal exfoliation (C/O ratio 1.53). Graphene oxide was modified with SO 2 (mMPGO) at 600 °C and by subsequent treatment at 200 °C having a sulfur content of 10.9% (C/O ratio 16.94) and manganese content 9.39 μmol•g −1 . The XPS spectrum of MPGO showed the presence of carbonyl and epoxide groups. The reactivity of mMPGO toward alkyl thiol and alkyl amine showed the same selectivity as other carbons and suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“… We have shown that the reduction of SO 2 on carbons occurs through two sequential paths: desulfurization and decarboxylation. These steps show a considerable difference in terms of energetic demand; the desulfurization of SO 2 occurs with a Δ G ‡ (40 °C) of 22.6 kcal·mol –1 while the decarboxylation of graphite has a barrier of Δ G ‡ (900 °C) = 114.3 kcal·mol –1 . For this reason, the ozonation reaction was studied at low temperatures to avoid ozone decomposition, and ozonized carbon was then submitted to decarboxylation.…”
Section: Resultsmentioning
confidence: 99%
“… We have shown that the reduction of SO 2 on carbons occurs through two sequential paths: desulfurization and decarboxylation. These steps show a considerable difference in terms of energetic demand; the desulfurization of SO 2 occurs with a Δ G ‡ (40 °C) of 22.6 kcal·mol –1 while the decarboxylation of graphite has a barrier of Δ G ‡ (900 °C) = 114.3 kcal·mol –1 . For this reason, the ozonation reaction was studied at low temperatures to avoid ozone decomposition, and ozonized carbon was then submitted to decarboxylation.…”
Section: Resultsmentioning
confidence: 99%